The future of the Eurozone: towards a European benchmark - Sara Casagrande; Bruno Dallago (Transformation, Integration and Globalization Economic Research (TIGER), 2021)
The European sovereign debt crisis has demonstrated the need for a rethinking of the European integration project. The strong variety between member countries prevented Eurozone to become a fiscal and political union and the asymmetric architecture of EMU revealed different weaknesses. The outbreak of the covid-19 emergency may represent a turning point for EU, and makes even more evident that the future of the Eurozone will depend also on the ability of member countries to make their institutional frameworks coexist. Helping member countries to achieve sustainable and stable outcomes, although in idiosyncratic ways, is the task of the European benchmark. It is a framework, inspired by European treaties, that aims to identify inefficiencies in terms of market, state and social failures and negative externalities inside economic, social and political institutions. This benchmark represents a new tool for a correct evaluation of the economic, social and political performance of the European member countries.
Keywords: F2; F5; O1; O4; 330; benchmark; European economic integration; European sovereign debt crisis; Eurozone; institutional variety